FUNGSI BAHASA DALAM SYAIR BIDASARI: KAJIAN SOSIOPRAGMATIK - Fauzi, Mohd (Jurnal Ilmu Budaya, 2015)
This writing deals with language functions which adops Leech concepts who uses five language functions. By using those concepts, this writing analyzes "Syair Bidasari" Sociopragmatically. The result shows that "Syair Bidasari" contains some language functions, they are informational, expressive, directive, aesthetic, andfatic language functions.